Advertisement Remove all ads

Solve for x : 1/((x-1)(x-2))+1/((x-2)(x-3))=2/3 , x ≠ 1,2,3 - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads

Solve for x

:`1/((x-1)(x-2))+1/((x-2)(x-3))=2/3` , x ≠ 1,2,3

Advertisement Remove all ads

Solution

`1/((x-1)(x-2))+1/((x-2)(x-3))=2/3`

`:.((x-3)+(x-1))/((x-1)(x-2)(x-3))=2/3`

`:.(x-3+x-1)/((x^2-2x-x+2)(x-3))=2/3`

`:.(2x-4)/((x^2-3x+2)(x-3))=2/3`

`:.(2x-4)/(x^3-3x^2-3x^2+9x+2x-6)=2/3`

`:.(2x-4)/(x^3-6x^2+11x-6)=2/3`

∴ 6x - 12 = 2x3 -12x2 + 22x - 12

∴ 2x3 - 12x2 + 16x = 0

∴ 2x(x2-6x+8) = 0

∴ (x2-6x+8) = 0

∴ x2 - 4x - 2x + 8 =  0

∴ x(x- 4)- 2(x - 4)= 0

∴ (x-4)(x-2)=0

∴ x-4=0 or x-2 = 0

∴ x = 4 or x = 2

Concept: Solutions of Quadratic Equations by Factorization
  Is there an error in this question or solution?
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×